Stress-strain response of high strength concrete and application of the existing models - Ayub, T. (Maxwell Science Publications, 2014)
Stress-strain model of concrete is essentially required during design phases of structural members. With the evolution of normal concrete to High Strength Concrete (HSC); various predictive models of stress-strain behavior of High Strength Concrete (HSC) are available in the literature. Such models developed by various researchers are differing to each other, because of the different mix proportions and material properties. This study represents a comparative analysis of available stress-strain models with the experimental results of three different series (100 cement concrete, Silica Fume (SF) concrete and Metakaolin (MK) concrete) of high strength concrete mixes. Compressive strength and stress-strain behavior of 100Ã200 mm cylinders made of all Prepared mixes was determined at with curing age of 28 days. Compressive strength of all mixes was found in the range of 71-87 MPa. Stress-strain behavior of tested cylinders was found much different from the available predictive models. In view of the dissimilarity occurred between the predictive stress-strain behavior and the experimental data; a new predictive model is proposed, which adequately satisfy the experimental results. Â© Maxwell Scientific Organization, 2014.